Association between composite dietary antioxidant index and migraine in American young women: insights from NHANES 1999–2004 cross-sectional data - Li, Zeyan; Zhang, Xinyu; Kong, Simin; Fu, Chuan-Chuan; Lv, Tian-Qi; Xiao, Bin (Frontiers in Neurology, 2024)
Background Excessive oxidative stress is one of the key pathophysiological mechanisms underlying migraine, and increasing antioxidant intake has proven to be an effective strategy for the prevention and improvement of migraine symptoms. To explore the relationship between the composite dietary antioxidant index (CDAI) and the occurrence of migraine attacks. Methods Cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999–2004 were utilized. Logistic regression, stratified analysis, and restricted cubic spline (RCS) models were employed to investigate the association between CDAI and migraine attacks. Results A total of 8,137 adults aged ≥20 were enrolled, comprising 1,610 patients with migraine and 6,527 non-migraine individuals. After adjusting for all covariates, CDAI was negatively correlated with migraine. In the overall participants, compared with the CDAI Q1 (−5.83 to −2.14) group, the adjusted odds ratio (OR) for migraine in Q3 (−0.59 to 1.53) and Q4 (1.53–44.63) groups were 0.71 [95% confidence interval (95% CI): 0.54–0.92, p = 0.011] and 0.64 (95% CI: 0.47–0.87, p = 0.005), respectively. After stratifying by age and gender, the protective effect was more pronounced in females aged 20–50, with adjusted OR for Q3 (−0.59 to 1.53) and Q4 (1.53–44.63) groups of 0.60 (95% CI: 0.40–0.90, p = 0.013) and 0.48 (95% CI: 0.30–0.78, p = 0.003), respectively. The RCS curve indicated a nonlinear relationship between CDAI and migraine in females aged 20–50, with a threshold of 0.006. Conclusion CDAI is negatively correlated with migraine attacks, and a higher CDAI may be an effective protective factor in preventing migraine attacks, especially in women aged 20–50.